Instytucja weta ludowego w Szwajcarii w kontekście projektu ustawy „Gripen-Fonds-Gesetz” - Kwella, Małgorzata; Marcia, Michalina (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2016)
The article presents issues connected with the popular referendum, also known as abrogative referendum, focusing on its functioning in the Swiss Confederation. It introduces the application of popular referendum, which is also collated with other institutions of direct democracy, provided for in the Swiss Constitution. As the abrogative referendum occasionally comes in for criticism from numerous backgrounds, the article confronts suggested disadvantages with application in practice based on the project of Swiss act known as „Gripen-Fonds-Gesetz”, taking also into consideration the distribution of votes and situation in individual cantons.
Keywords: Direct Democracy; Gripen; abrogative referendum; popular vote; Switzerland; popular referendum